PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SDN MODEL TERPADU MADANI - Ni Made Sutriyanti; Astija; Muh. Yusuf (LPPM Universitas Cipta Mandiri, 2025)
This study aims to describe the steps of implementing the Problem Based Learning model in improving students' critical thinking skills in grade 4 of Madani Integrated Model Elementary School. The Classroom Action Research (PTK) that will be implemented consists of two cycles. Cycle I includes planning stage I, action implementation I, observation I, and reflection I. This study is a form of research that focuses on action in the classroom. This Classroom Action Research was conducted at Madani Integrated Model Elementary School located in Palu City. The objects in this study include critical thinking skills and student learning outcomes. This research focused on grade 4 students at Madani Integrated Model Elementary School consisting of 30 students, with details of 19 female students and 11 male students. The application of the Problem Based Learning learning model has the potential to improve students' critical thinking skills and learning outcomes in solving story problems in mathematics subjects in grade 4 at Madani Integrated Model Elementary School. This can be proven by the mastery of critical thinking skills showing an increase from the initial value of 63.8 (quite critical) to 78.6 (critical) in the final condition. The percentage of students who thought critically in the initial condition was 40.00%, which then increased in the final condition to 56.67%.